Synthesis of ethyl (R)-4-chloro-3-hydroxybutyrate by immobilized cells using amino acid-modified magnetic nanoparticles. (December 2020) - Lu, Yuan; Dai, Hongqian; Shi, Hanbing; Tang, Lan; Sun, Xingyuan; Ou, Zhimin
Graphical abstract: Highlights: Ethyl ( R )-4-chloro-3-hydroxybutyrate was synthesized by Fe3O4-Arg-Cells. Arginine is a desirable chemical as ligand anchored with magnetic nanoparticles. Fe3O4-Arg-Cells like microscopic stirrers in an alternating magnetic field. Continuous reaction in magnetic fluidized bed reactor improved catalyst efficiency. Abstract: Fe3 O4 -Arg was selected as the optimal carrier due to its high activity recovery of immobilized cells in the preparation of Fe3 O4 -Arg-Cells. The optimal immobilization conditions for the preparation of Fe3 O4 -Arg-Cells were 30 °C, 4 h, pH 7, and 3 g dry yeast. The activity recovery of immobilized cells reached 76.8 %. For a batch reduction in a shaker in an alternating magnetic field, Fe3 O4 -Arg-Cells were used as a catalyst to gain ethyl ( R )-4-chloro-3-hydroxybutyrate (( R )-CHBE). For further improvement in reduction productivity, a continuous reduction in the magnetic fluidized bed reactor system (MFBRS) was completed. Under their optimal transformation conditions, it took 24 h for Fe3 O4 -Arg-Cells to complete the conversion of ethyl 4-chloro-3-oxobutanoate (COBE) (0.8553 mol/L) in the shaker and only 8 h for the batch reduction in an alternating magnetic field. Continuous reduction in MFBRS provided new ideas for the efficient production of ( R )-CHBE; 1.5882 mol/L (10 mL) of COBE can be completely converted in 6 h. The conversion and enantiomeric excess (e.e.) of ( R )-CHBE were 100 % and above 99.9 % respectively, in the three reaction systems mentioned above.